Cognate facilitation effects in trilingual word recognition - Szubko-Sitarek, Weronika (Studies in Second Language Learning and Teaching, 2011)
Research on bilingual word recognition suggests that lexical access is nonselective with respect to language, i.e., that word representations of both languages become active during recognition. One piece of evidence supporting nonselective access is that bilinguals recognize cognates (words that are identical or similar in form and meaning in two or more languages) faster than noncognates. In fact, any difference between how cognates and ‘monolingual’ words are processed by multilinguals would indicate that the other, currently irrelevant language must have played a role as well, at least as long as the two groups of words are comparable with respect to all dimensions other than language membership. The aim of the present paper is to report on two visual perceptual experiments conducted within the lexical decision task paradigm whose aim was to test the assumptions concerning the special position of cognates (the cognate facilitation effect, cf. Dijkstra, 2005) within a trilingual mind and to answer the question whether trilinguals rely upon their second language lexical knowledge when recognizing L3 words. The results of the experiments attest to simultaneous activation and parallel processing as well as interaction among all the three languages. At the same time, they point to the fact that cross-linguistic lexical access and the source and strength of transfer may be constrained by variables such task demands.